ENHANCING STUDENTS’ AURAL COMMUNICATION SKILL THROUGH ROLE PLAY TECHNIQUE AS THE LEARNING MODEL - Haris Budiana (Universitas Majalengka, 2017)
Teaching speaking to the first year students of English Department is intended to give basic competence in communication in English to the students. In the effort of upgrading the students’ ability in spoken language, the writer as the lecturer takes the topic of the research about the learning model of role play to increase the students’ aural communication skill. The research is purposed to describe how the role play as the classroom activities should be done in the classroom as well as the impact. The method of the research is the experimental method. The writer took 25 students. The technique of collecting the data that the writer used in order to support the research was pre-test and post-test. The result showed that the learning model of role-playing encouraged students to memorize, drill the expressions, and act out the roles. The data of scoring through analytical method was analyzed by using t-test formula. From the analysis of t-observed, it was found that the role-play technique was able to lead the students toward the better speaking performance. It means that the role-play technique has significant impact on the students’ face to face communication skill. In other words, the students found it helpful to perform their aural communication skill through role-playing.